Análise dos padrões de ocorrência do mico-leão-preto (Leontopithecus chrysopygus) na Bacia do Alto Paranapanema - Melo, Stephany Ribeiro de (Universidade Federal de São Carlos, 2023)
Habitat loss and fragmentation has been a reality faced by many natural landscapes. This scenario results in negative impacts on natural ecological processes, such as individual dispersion across landscapes, which plays a major role in genetic diversity, reproduction and species distribution. Changes in land use and cover has been one of the main factors responsible for altering these natural processes, in addition to reductions of the native habitats for many species. The Alto Paranapanema Basin is one of the examples of these anthropogenic landscapes in which natural areas are reduced and fragmented and landscapes become occupied by other land uses. This region, which still holds large blocks of the Atlantic Forest biome, is home of many endemic and endangered species, such as the Leontopithecus chrysopygus (black lion tamarin). The present work aimed to analyze the patterns of occurrence of the species in the years 1987 and 2017, considering structural and functional characteristics of the landscape. In order to achieve this objective, landscape metrics were applied to understand the spatial changes of the landscape, and graph theory was used to determine the functionally connected area, considering the dispersal capacity of the species. The results showed that the black lion tamarin occurs, on average, in fragments larger than 500 ha, and this value is significantly larger than the average available fragments in the landscape (approximately 5 ha). However, when considering the ability to disperse between fragments, the species manages to reach large functionally connected areas, reaching home ranges greater than 1,000 ha in particular regions of the landscape. This connectivity is generally promoted by small fragments that are arranged between large patches of habitats, forming corridors (mainly Permanent Protection Areas - APPs), which allow individuals to reach different forest fragments. In addition, it was noted that part of the matrix surrounding the fragments is predominantly forestry, indicating that the species may also be using these areas to disperse and reach fragments of native vegetation. These results suggest that the implementation of ecological corridors is a good and viable alternative for increasing the home range of the black lion tamarin, mainly through the restoration of riparian APPs.
Black lion tamarin (Leontopithecus chrysopygus) occurrence patterns in the Alto Paranapanema Basin
Keywords: Conectividade funcional; Mico-leão-preto (Leontopithecus chrysopygus); Alto Paranapanema; Corredor ecológico; Paisagem fragmentada; Perda e Fragmentação do habitat; Mata Atlântica; Silvicultura; Functional connectivity; Black lion tamarin (Leontopithecus chrysopygus); Ecological corridors; Fragmented landscapes; Habitat loss and fragmentation; Atlantic Forest; Forestry; CIENCIAS BIOLOGICAS::ECOLOGIA